2018
DOI: 10.1590/s1678-9946201860050
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of zinc in the visceromegaly regression and recovery of hematological parameters during treatment of visceral leishmaniasis in children from an endemic area

Abstract: Leishmaniasis is a disease complex with various clinical symptoms caused by different species of parasites of the genus Leishmania. The visceral form of the disease, characterized by severe symptoms is fatal, if not treated. The high toxicity of current antileishmanial drugs and the need for long-term treatment make the therapy complicated, especially in a large number of infected children. Hence, the search for new therapies must be intensified. Oral administration of the trace element zinc has been considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Kala-azar patients reported low serum levels of vitamin A and zinc [31]. Improved clinical outcome of the disease was reported in children with kala-azar who received zinc supplementation along with amphotericin B or pentavalent antimonial treatment [32,33]. The serum levels of vitamin A, vitamin D, zinc, and iron improve the treatment outcomes in systemic leishmaniasis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Kala-azar patients reported low serum levels of vitamin A and zinc [31]. Improved clinical outcome of the disease was reported in children with kala-azar who received zinc supplementation along with amphotericin B or pentavalent antimonial treatment [32,33]. The serum levels of vitamin A, vitamin D, zinc, and iron improve the treatment outcomes in systemic leishmaniasis [34].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with those described in the literature 21 , 22 , 54 . Carbone et al 55 showed that children with kala-azar who received zinc supplementation during amphotericin B or pentavalent antimonial treatment showed faster clinical improvement than the group that did not receive zinc supplementation. However, a recent systematic review did not find any study that assessed the effects of oral nutritional supplements in patients with VL treated with antileishmanial drug therapy 56 .…”
Section: Discussionmentioning
confidence: 99%